Classification of child abuse by motive and degree rather than type of injury. Issue 2 (1st February 2003) - Southall, D P; Samuels, M P; Golden, M H
Abstract : The protection of children may be enhanced if ill treatment is classified by motive and degree rather than by type of injury. Four categories are proposed: A, abuse: premeditated ill treatment undertaken for gain by disturbed, dangerous, and manipulative individuals; B, active ill treatment: impulsively undertaken because of socioeconomic pressures, lack of education, resources, and support, or mental illnesses; C, universal mild ill treatment: behaviour undertaken by all normal caring parents in all societies; and D, neglect: defined here as an unintentional failure to supply the child's needs. Such a classification could clarify the procedures for investigation and protection, and support the creation of a Special Interagency Taskforce on Criminal Abuse (SITCA) for those suspected of abuse (category A).